2017
DOI: 10.18535/jmscr/v5i4.79
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Zinc Toxicity as a Complication of Phototherapy

Abstract: BackgroundUnconjugated bilirubin deposition in the neuronal membrane leads to permanent neuronal injury. Primary aim of detecting and treating neonatal hyperbilirubinemia is the prevention of bilrubin encephalopathy and its chronic sequalae. Therapeutic options for unconjugated hyperbilirubinemia in neonates, like phototherapy and blood exchange transfusion are costly, time-consuming and potentially risky. New therapeutic methods appear to be necessary to decrease elevated serum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
4
3
0
Order By: Relevance
“…There was a significant increase in the percentage of neonates with zinc levels > 200 mg/dL after phototherapy (before phototherapy 3 (4%) neonates, after phototherapy 10 (15%) neonates. This agrees with [14] who found that, Phototherapy was associated with a significant increase in the serum zinc level in neonates with severe hyperbilirubinemia (TSB >18 mg/dL) but not in those with mild moderate hyperbilirubinemia (TSB<18 mg/dL). In addition, phototherapy caused a significant increase in the rate of zinc with potentially toxic levels (zinc > 200) in only neonates with severe hyperbilirubinemia.…”
Section: Discussionsupporting
confidence: 92%
“…There was a significant increase in the percentage of neonates with zinc levels > 200 mg/dL after phototherapy (before phototherapy 3 (4%) neonates, after phototherapy 10 (15%) neonates. This agrees with [14] who found that, Phototherapy was associated with a significant increase in the serum zinc level in neonates with severe hyperbilirubinemia (TSB >18 mg/dL) but not in those with mild moderate hyperbilirubinemia (TSB<18 mg/dL). In addition, phototherapy caused a significant increase in the rate of zinc with potentially toxic levels (zinc > 200) in only neonates with severe hyperbilirubinemia.…”
Section: Discussionsupporting
confidence: 92%
“…About our primary outcomes, the present study showed that serum zinc level increased significantly after phototherapy in our study group (75.45 ± 14.94; p-value < 0.001). This is in concordance with Saravanan and Raghuram (15) who performed a prospective cohort study to estimate serum zinc level alterations before and after phototherapy, in jaundiced newborns. Their results showed that phototherapy was associated with a significant increase in serum zinc level in neonates with (TSB >18 mg/dL) but not in those with (TSB<18 mg/dL).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, our analysis showed that the duration of phototherapy was 2.4 ± 0.5 days, which is similar to Mosayebi et al (14) and Saravanan and Raghuram (15) where the duration was 2.4 ± 0.6 days in both studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations